Application of Criminal Sanctions to Murder Cases According to Islamic Criminal Law - Ilham Maulana; Ferdi Reynaldi; Deni Afriansyah; M. Ramzy Fernanda; Zaid Alfauza Marpaung (Jurnal Cendikia ISNU SU, 2024)
The application of criminal sanctions in murder cases according to Islamic criminal law is a form of justice that balances the rights of the victim, the perpetrator, and the community. Islamic criminal law divides murder into three main categories: intentional murder (qatl 'amd), semi-intentional murder (qatl syibh 'amd), and unintentional murder (qatl khath'). Each type of murder has different legal consequences, with the main sanctions being qiyhas (retribution) for intentional murder, and diyat (financial compensation) and kaffarah (atonement) for semi-intentional and unintentional murder. This article aims to analyze the application of criminal sanctions in various murder cases from an Islamic legal perspective, and to explore the principles of justice, forgiveness, and the opportunity for peaceful resolution accommodated by the diyat mechanism. This study then compares sanctions in Islamic criminal law with those in modern criminal law systems, highlighting the uniqueness of the Islamic approach that prioritizes the balance between punishment and forgiveness. In conclusion, Islamic criminal law offers a flexible yet firm model of law enforcement, where justice does not only involve revenge, but also provides opportunities for reconciliation and peace.